Volatile compounds trigger the pleasant strong aroma of new cultivar Gama Melon Parfum during growth and maturation - Umar Hafidz Asy'ari Hasbullah; Supriyadi Supriyadi; Budi Setiadi Daryono (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
Melon (Cucumis melo L.) cv. Gama Melon Parfum (GMP) is the new cultivar from cross-breeding of Natsuno Omoide (NO3) female parent and Miyamauri (MR5) male with phenotypic characteristics that is prominent such as very strong pleasant aroma when ripe. The physiological characteristics will be changed which have an impact on the formation of volatile compounds during fruit development. Therefore, the profile of strong volatile aroma compounds during fruit development to is critical to be identified. The volatile compounds analysis was performed on fruits harvested at 7, 14, 21, 28, and 35 days after pollination and storage at -20°C. Gas chromatography-mass spectrometry (GC-MS) was used for volatile identification. The results showed some volatile compounds changed during fruit development consisted of 8 esters, 2 alcohols, 1 acid, 3 terpenoids, and 3 hydrocarbons. The profile of volatile compounds was dominated by esters, followed by alcohols and acid respectively. Interestingly, the characteristics of the volatile compounds can differentiate between the ripe stage and unripe stage using principal component analysis. The findings of this study can be used to improve the quality aroma of GMP.